2003
DOI: 10.1074/jbc.m303679200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CD4 Down-modulation by Late Stage HIV-1 nef Alleles Is Associated with Increased Env Incorporation and Viral Replication

Abstract: Three viral proteins participate in the down-modulation of CD4 in human immunodeficiency virus type 1 (HIV-1)-infected cells. The underlying mechanisms have been extensively investigated. However, the physiological relevance of this phenomenon remains poorly understood. To address the role of CD4 down-modulation in HIV-1 pathogenesis in vivo, we have characterized the functional properties of nef alleles isolated from seven HIV-1-infected patients at either the stage of AIDS (late alleles) or during the asympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 61 publications
(45 reference statements)
10
73
1
3
Order By: Relevance
“…We propose that, through removal of CD4 from the cell surface, Nef enhances viral infectivity by facilitating the incorporation of gp120 into nascent virions and by preventing virion incorporation of CD4. Similar conclusions were reached in studies by Lama and coworkers (4,39), who showed that expression of CD4 in 293T and Jurkat cells inhibited the incorporation of Env into HIV-1 particles and that Nef overcame the inhibition by downregulating CD4 expression. Our findings extend these conclusions to a physiologically relevant cell type, primary CD4 ϩ T cells.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We propose that, through removal of CD4 from the cell surface, Nef enhances viral infectivity by facilitating the incorporation of gp120 into nascent virions and by preventing virion incorporation of CD4. Similar conclusions were reached in studies by Lama and coworkers (4,39), who showed that expression of CD4 in 293T and Jurkat cells inhibited the incorporation of Env into HIV-1 particles and that Nef overcame the inhibition by downregulating CD4 expression. Our findings extend these conclusions to a physiologically relevant cell type, primary CD4 ϩ T cells.…”
Section: Discussionsupporting
confidence: 71%
“…Analysis of the Nef genes isolated from infected individuals and monkeys have shown that major histocompatibility complex (MHC) class I downregulation is a common feature of Nef isolates present at early stages of infection (10,51). In contrast, CD4 downregulation is more highly conserved in Nef genes from late stages of HIV and SIV infection (4,55) and in AIDS patients (10,66). Together, these studies suggest that while MHC I downregulation by Nef is important for HIV-1 persistence during the early asymptomatic phase of HIV-1 infection, downregulation of CD4 is more important for HIV-1 replication during late symptomatic stages of HIV-1 disease, when X4-tropic HIV-1 strains emerge.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CD4 expressed on the surface of infected cells has the potential to impair HIV-1 replication by (i) inhibiting the release of progeny virions (48), (ii) impairing the incorporation of Env into nascent virions (6,29), and (iii) sequestering Env from the virion budding site (3,6,29,31,32). We confirmed that CD4 suppresses the production of infectious virions (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…We have demonstrated that the ability of Nef to enhance HIV-1 replication in ex vivo-infected human lymphoid tissue correlates with its functional activity in CD4 downmodulation (25). This Nef function might be critical for the production of fully infectious viral particles from CD4 ϩ T cells (6). Vpu might enhance viral spread by both the same and different mechanisms because it downmodulates CD4 (34, 53) but it also increases the release of virus particles (49,54).…”
Section: Productively Infected Cd4mentioning
confidence: 99%